2005
DOI: 10.1523/jneurosci.1777-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Epileptiform Discharges Induced by Altered Group I Metabotropic Glutamate Receptor-Mediated Synaptic Responses in Hippocampal Slices of a Fragile X Mouse Model

Abstract: Mutations in FMR1, which encodes the fragile X mental retardation protein (FMRP), are the cause of fragile X syndrome (FXS), an X-linked mental retardation disorder. Inactivation of the mouse gene Fmr1 confers a number of FXS-like phenotypes including an enhanced susceptibility to epileptogenesis during development. We find that in a FXS mouse model, in which the function of FMRP is suppressed, synaptically released glutamate induced prolonged epileptiform discharges resulting from enhanced group I metabotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
185
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(201 citation statements)
references
References 33 publications
(51 reference statements)
15
185
1
Order By: Relevance
“…Next, we examined if this LTP deficit could be caused by abnormal action potential firing in LA neurons, because mGluRs are known to underlie pathological firing patterns in the hippocampus of Fmr1 KO mice (22). We detected no difference in EPSP-Spike (E-S) coupling, an index of the probability of firing an action potential for a given synaptic strength (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Next, we examined if this LTP deficit could be caused by abnormal action potential firing in LA neurons, because mGluRs are known to underlie pathological firing patterns in the hippocampus of Fmr1 KO mice (22). We detected no difference in EPSP-Spike (E-S) coupling, an index of the probability of firing an action potential for a given synaptic strength (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…In Fmr1 KO mice, dysregulated neuronal connectivity in the barrel cortex (Bureau et al, 2008) leads to defective glutamatergic synapse maturation, delayed and aberrant formation of sensory maps, and altered synaptic plasticity during the critical period (Harlow et al, 2010). In general, loss of FMRP seems to lead to altered network synchrony and hyperexcitable neuronal networks (Chuang et al, 2005;Gibson et al, 2008).…”
Section: Altered Neuronal Network Formation In Fxsmentioning
confidence: 99%
“…Subsequent work also suggested that apart from hippocampal LTD, additional mGlu 1/5 -dependent neuronal mechanisms are dysregulated in the FXS brain. In the hippocampus, deletion of FMRP was shown to lead to prolonged epileptiform discharges caused by enhanced sensitivity of mGlu 1/5 to synaptically released glutamate (Chuang et al, 2005). Loss of FMRP also leads to changes in mGlu 1/5 -mediated endocannabinoid (eCB) synthesis and release in the hippocampus (Zhang and Alger, 2010).…”
Section: Other Mglu 1/5 -Dependent Mechanisms In Fxsmentioning
confidence: 99%
“…In the case of mGluR5-dependent protein synthesis, one of these negative regulators might be FMRP. In the absence of FMRP, one might expect that the protein synthesis-dependent consequences of mGluR5 activation would be exaggerated-and indeed this is the case (Huber et al, 2002;Chuang et al, 2005).…”
Section: Metabotropic Glutamate Receptormentioning
confidence: 99%